MENGATASI PERILAKU MEMBOLOS MELALUI KONSELING BEHAVIORISTIK DENGAN TEKNIK BEHAVIOR CONTRACT - Karyanto, Karyanto; Masturi, Masturi; Kiswantoro, Arista (Universitas Muria Kudus, 2023)
It be conducted at SMP Negeri 2 Sukolilo with two students as the research subjects. Data collection techniques include interviews, observation, and documentation. Based on the results of the study, it is found that the internal factors causing truancy behavior are personal problems that underlie the behavior of each counselee. Counselee I has an external factor, which is the influence of peers and their home environment. Counselee II is caused by the factors of discrimination and lack of support from those around them. From the results, it can be concluded that truancy behavior includes many factors, including personal factors, family factors, environmental factors, and socio-economic factors. It is important to address the factors that can influence students' truancy behavior by understanding the underlying issues and providing appropriate and relevant support, both in terms of mental and emotional health, academic support, family support, and positive and inclusive educational environment support